Exploring the prevalence of developmental reading difficulties in Children with Fetal Alcohol Spectrum Disorders - Bromley, Katie Rachael (Department of Psychology, 2014)
Background. As part of a large ongoing research programme concerned with the teratogenic effects prenatal alcohol exposure has on the developing brain, this study investigated whether developmental reading difficulties are present in school-going children with fetal alcohol spectrum disorders (FASD). Whereas the diagnostic facial anomalies associated with FASD are well documented, cognitive deficits remain largely unexplored. Some neuropsychological reviews include deficits in reading as part of the FASD cognitive profile; however, the extant empirical research investigating reading abilities in children with FASD is limited. Therefore, the specific objectives of the current study were to explore the prevalence and characteristics of developmental reading skill deficits in a sample of children with FASD. Methods. Participants were 46 children (9-13 years) who had previously been diagnosed as either prenatally exposed or non-exposed. Of the 32 exposed children, 7 met the criteria for fetal alcohol syndrome (FAS), 3 met the criteria for partial FAS (pFAS) and 22 did not meet the criteria for diagnosis of FAS/pFAS but were still heavily exposed (and were thus characterized as âother heavily exposedâ, or OHE). All participants were administered the Neale Analysis of Reading Ability (NARA; a measure of reading speed, accuracy, and comprehension) and the Phonological Assessment Battery (PhAB; a measure of phonological awareness, processing speed and fluency). Independent samples t-tests and one-way analyses of covariance (ANCOVAs) were performed to determine if there were statistically significant between-group differences in a two-group (exposed versus non-exposed) or three-group (FAS/pFAS versus OHE versus control) comparison. Multiple regression-based analyses were performed to determine if a relationship existed between a continuous measure of prenatal alcohol exposure and the outcome measures. Within each of these analyses an estimate of IQ was used to determine if the effects seen were present even with that covariate taken into account. Results. None of the two- or three-group analyses showed any statistical significance on the PhAB or NARA outcome variables. Participants in the FAS/pFAS and OHE groups performed significantly differently on the PhAB non-phonological fluency performance measure; this between-group difference was not in the predicted direction, however, and probably resulted from artifactual factors. Results from the multiple regression-based analyses showed that associations between the predictor variable (level of prenatal alcohol exposure) and two outcome variables (phonological production speed and reading rate abilities) approached, but did not reach, statistical significance. 7 Conclusion. Overall, the data suggest that impairments in phonological awareness, phonological processing speed, verbal fluency, and developmental reading difficulties are not characteristic of the cognitive profile of children with FASD. These findings are not conclusive, however, due to several limitations in the current study. These limitations are discussed and provide interesting insight into the process of assessing phonological abilities and reading skills in this population. Further research, using a broader range of assessment tools and a larger sample size, is necessary in order to provide a more detailed and definitive analysis of these abilities. Nonetheless, the current study shows that the evaluation of reading and phonological disorders in FASD is an important and worthwhile endeavour.